2010
DOI: 10.1016/j.adt.2010.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Oscillator strengths and transition probabilities of O II

Abstract: The abundance of singly ionized oxygen, O II, in planetary nebulae provides crucial diagnostic tests for the physical conditions present in these astrophysical environments. The abundance can be determined from the absorption lines formed by the radiative processes, such as the photo-excitations reported here. Radiative transitions are obtained from a total of 708 fine structure levels of O II with n ≤ 10, l ≤ 9, and 1/2 ≤ J ≤ 17/2. For spectral analysis oscillator strengths, line strengths, and transition pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…is that LS coupling is not assumed. More recently, non-LS oscillator strengths have become available through the Iron Project (Hummer et al 1993), and work done by the atomic-data group at Ohio State University (Nahar 2010). Other important sources of radiative data for Fe include Becker & Butler (1992, Nahar (1995).…”
Section: Discussionmentioning
confidence: 99%
“…is that LS coupling is not assumed. More recently, non-LS oscillator strengths have become available through the Iron Project (Hummer et al 1993), and work done by the atomic-data group at Ohio State University (Nahar 2010). Other important sources of radiative data for Fe include Becker & Butler (1992, Nahar (1995).…”
Section: Discussionmentioning
confidence: 99%
“…The ξ -factors for carbon were calculated with the use of photoionization cross section from [10] assuming the local thermodynamic equilibrium (LTE). The results are shown in Fig.…”
Section: Photon Absorptionmentioning
confidence: 99%
“…Lines with the upper terms 3d 4 P and 3d 4 D also tend to be underestimated in our calculations, and the reason appears to be uncertainties in the transition probabilities. The A values for these terms calculated by Nahar () are significantly lower than those quoted in the NIST data base from Veres & Wise () and Bell et al (). The NIST values give a much better – albeit insufficient – match to observations with predicted intensities 0.09–0.4 times the measured value, far below the assumed observational uncertainty.…”
Section: Resultsmentioning
confidence: 61%
“…We used the transition probabilities of Nahar () supplemented with the intermediate‐coupling calculations for the 3d–4f array by Liu et al (), who found significant effects of LS coupling breakdown in 4f and some 3d terms. Terms with l ≥ 3 are better described in LK coupling (Wenåker ).…”
Section: Atomic Datamentioning
confidence: 99%